Hardness of heat-polymerized acrylic resins after disinfection and long-term water immersion - Neppelenbroek, K. H.; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Giampaolo, E. T. (Mosby, Inc, 2005)
Statement of the problem. In selecting a disinfectant for dental prostheses, compatibility between the disinfectant and the type of denture base material must be considered to avoid adverse effects on the hardness of the acrylic resin.Purpose. This study investigated the hardness of 2 denture base resins after disinfection and long-term water immersion.Material and methods. Thirty-two disk-shaped specimens (13 mm in diameter and 8 mm thick) were fabricated from each resin (Lucitone 550 and QC-20), polished, stored in water at 37degreesC for 48 hours, and submitted to hardness tests (Vickers hardness number [VHN]) before disinfection. Disinfection methods included scrubbing with 4% chlorhexidine gluconate for 1 minute, immersion for 10 minutes in I of the tested disinfectant Solutions (n=8) (3.78% sodium perborate, 4% chlorhexidine gluconate, or 1% sodium hypochorite), and immersion in water for 3 minutes. The disinfection procedures were repeated 4 times, and 12 hardness measurements were made on each specimen. Control specimens (not disinfected) were stored in water for 56 minutes. Hardness tests (VHN) were also performed after 15, 30, 60, 90, and 120 days of storage in water. Statistical analyses of data were conducted with a repeated measures 3-way analysis of variance (ANOVA) and Tukey post-hoc test (alpha=.05).Results. Mean values +/- SD for Lucitone 550 (16.52 +/- 0.94 VHN) and QC-20 (9.61 +/- 0.62 VHN) demonstrated a significant (P<.05) decrease in hardness after disinfection, regardless of material and disinfectant solutions used (Lucitone 550: 15.25 +/- 0.74; QC-20: 8.09 +/- 0.39). However, this effect was reversed after 15 days of storage in water. Both materials exhibited a continuous increase (P<.05) in hardness values for up to 60 days of water storage, after which no significant change was observed.Conclusion. Within the limitations of this in vitro study, QC-20 and Lucitone 550 specimens exhibited significantly lower hardness values after disinfection regardless of the disinfectant solution used.